Circulation model for water circulation and purification in a water Cerenkov detector - 路浩奇 杨长根 王玲玉 徐吉磊 王瑞光 王志民 王贻芳 (Chinese physics C, 2009)
Owing to its low cost and good transparency,highly purified water is widely used as a medium in large water Cerenkov detector experiments. The water circulation and purification system is usually needed to keep the water in good quality. In this work,a practical circulation model is built to describe the variation of the water resistivity in the circulation process and compared with the data obtained from a prototype experiment. The successful test of the model makes it useful in the future design and optimization of the circulation/purification system.